Zinc: Prophylaxis and Treatment for the Common Cold - Szymon Piaszczyński; Kacper Płeska; Joanna Wojtania; Michał Łepik; Zofia Uszok; Krzysztof Rosiak; Kacper Reguła; Kamil Waloch; Andrzej Czajka; Bartłomiej Szymański (Nicolaus Copernicus University in Toruń, 2024)
The common cold is a widespread and frequent illness with limited treatment options, generating costs for individuals and society. A crucial goal is an effective symptomatic treatment and reducing the duration of the illness, which can bring significant global benefits. Several studies suggest that using zinc lozenges within 24h of symptom onset can noticeably shorten the duration of symptoms. Zinc has a complex and not fully understood role in immune regulation. Zinc lozenges are inexpensive, easily accessible, and has few side effects. Based on numerous studies, zinc lozenges seem to be a noteworthy option for symptomatic treatment. The application of therapy in athletes can be of particular importance due to the faster recovery and the avoidance of missing training sessions.